ANALISIS TREND EFISIENSI DAN EFEKTIFITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI KOTA SURAKARTA PERIODE TAHUN 1995 - 2005 - Magdalena Nany; Endang Satyawati; Fitri lndrawati Soetanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
The objective of this research was to analyze the trend of the efficiencyofland and building tax collection in Surakarta city. This research was also intended to analyze the trend ofthe effectiveness ofland and building tax collection in Surakarta city. Annual land and building tax data during 1995 - 2005 were analyzed by trend analysis using least square method. The results show that the efficiency ofland and building tax collection in Surakarta city during 1995 - 2005 tend to decline. The results also show that the effectiveness ofland and building tax collection in Surakarta city during 1995 - 2005 tend to decline.